Shaping interaction among improved cowpea’s farming: Do Institutions have a role to play? A case of Oyam district in Uganda - Tobby, Akecha; Prossy, Isubikalu; Losira, N. Sanya; Narisi, Mubangizi; Jacob, G Agea; Eton, Marus (Journal of Agricultural Extension and Rural Development, 2022)
This paper examines the roles played by institutions in shaping the interactions among improved cowpea farmers in Oyam district. A cross sectional research design and qualitative approach was used. Focus Group discussions were held and members were purposely selected. The study found out that the cowpea farmers normally provide and share farm saved seeds preserved from the previous harvest with fellow farmers while these seeds are un-inspected by a technical person. Cowpea farmers believe in trust and rely on fellow farmers for source of seeds or technical information on the agronomic and post-harvest practices and potential market opportunities. Cowpea farmers remained vulnerable to unreliable supply of certified input (seeds), and resorted to own farm saved seeds and make them more susceptible to counterfeit cowpea seeds and other input. The poor performance of counterfeit input (seeds) supplied to cowpea farmers by fellow farmers and other counterfeit input dealers made farmers loose trust on formal input supplies and depended more on the on-farm saved seeds from fellow farmers recycled over time. The study recommends that the district local government should put in place the formal institutions that would ensure other actors understands the incentives and disincentives so as to re-align individual interests, create actors’ inter-dependence in a bid to improve on the competitiveness of improved cowpea. The concerned agencies should strengthen the registration of actors engaged in the development and promotion of innovation at the lower local government and ensure traceability of input used by farmers to stream line actors’ roles.